A Learning Strategy Use and Speaking Skills in the Indonesian Context - Sri Wahyuni (Department of English Language Education, UIN Sunan Ampel Surabaya, 2019)
Abstract—This study investigates language learning strategies used by Indonesian tertiary students in learning to speak English. The study addresses what learning strategies the students use; what strategy group and individual strategy they favour; and whether speaking skills significantly affect strategy use. This paper reports the quantitative results of a larger mixed-methods study drawing on questionnaire (n = 65) and students’ speaking grades (n = 65) obtained from students at Gajayana University of Malang in Indonesia. The study demonstrates that the students used a wide range of strategies that spread over six strategy groups of Oxford’s taxonomy (1990). Advanced and elementary students favoured compensation strategies, and intermediate students, metacognitive strategies. As regards individual strategy, advanced students favoured ‘using a circumlocution or synonym’; intermediate students, ‘paying attention’; and elementary students, ‘using resources for receiving and sending messages’. The study also shows that speaking skills significantly affected the use of affective strategies only. The paper concludes by discussing implications for theory and practice.